2021
DOI: 10.1088/1742-6596/2042/1/012150
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Metrics for Scenario-based Robustness Assessment of Building Performance

Abstract: To decrease greenhouse gas emissions of the Swiss building stock, effective retrofit strategies are necessary. Due to the long-term operation of buildings, future developments and uncertainties need to be considered, which calls for assessing the robustness of retrofit decisions. Existing studies propose robustness metrics for decisions under deep uncertainty to be coupled with a scenario-based simulation approach. We review these metrics and present a simulation approach that includes current and future opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Further, in previous studies, we have compared retrofit design options for the Swiss context with scenarios on occupancy, climate, and decarbonization [15,31]. We found that decarbonization scenarios are especially relevant and that the heating system choice majorly affects robustness.…”
Section: A Imentioning
confidence: 91%
See 3 more Smart Citations
“…Further, in previous studies, we have compared retrofit design options for the Swiss context with scenarios on occupancy, climate, and decarbonization [15,31]. We found that decarbonization scenarios are especially relevant and that the heating system choice majorly affects robustness.…”
Section: A Imentioning
confidence: 91%
“…Choosing other scenarios might result in other findings. The choice of maximum regret as a metric for robustness is based on literature and our previous findings [28,31], but other metrics would also be possible.…”
Section: Limitations Of the Methodological Approachmentioning
confidence: 99%
See 2 more Smart Citations